CONTEXTUALISING KNOWLEDGE AS THE BASIS OF NEW MODEL SCHOOL TEACHER PREPARATION - Stefanova, Natalija; Shubina, Natal’ja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Processes of convergence and integration that characterize contemporary society naturally seep into the education system, first of all at school. Proof of this are the modern State educational standards for general education in Russia, which focuses on the formation, along with subject, metasubject  educational results. However, the preparation of teachers is based on subject principle, which hampers the realization of interdisciplinary integration laid down in standards. Increase massif operated knowledge from different disciplinary areas requires new approaches to formation of teachers’ professional skills, primarily, the ability to constantly replenish and build their personal knowledge. Currently, the development of creative abilities of presentation and interpretation training information that is interdisciplinary in nature. An interdisciplinary approach in teaching alters the level and quality of learning. The basis for this approach in the preparation of teachers can become idea of knowledge contextualization. The aim of this paper is theoretical and experimental justification of the need to build a new model of teacher preparation, capable to participate in solving the problems of the integration of school subjects. Methods of theoretical analysis (system, historical and problematic), as well as methods of design and experimental work are used. The article presents the results of experimental work undertaken to search for a new model of teacher preparation, capable to participate in the integration of school subjects (for example mathematics and Russian language), concepts, laid down in model building, revealed the prior directions of its implementation.